DIPLOMASI KOMERSIAL INDONESIA UNTUK MENDORONG INVESTASI DARI AMERIKA SERIKAT DI INDUSTRI MAKANAN DAN MINUMAN 2018-2021 - Farhani Syuja'I Khoir (2023)
Foreign Direct Investment is one of the activities that support the economic country. Through FDI a country will enter a transition phase towards an industrial scale. This research aims to find out and understand the commercial diplomacy carried out by Indonesia in encouraging investment realization from the US in the food and beverage industry sector 2018-2021. Indonesia is a developing country with potential that is supported by various aspects. There is an investment or foreign direct investment in terms of supporting the wheels of the economy to meet national targets. The implementation of economic diplomacy has become one of the main overseas activities emphasized in President Joko widodo period. Based on data from BKPM says that the investment value from the United state in the F&B sector has decreased from 2013-2018 where the purpose of this study is to find out how the implementation of diplomacy is carried out in order to push back the investment value. This research contains aspects that are owned by Indonesia, and a series of diplomatic implementations carried out by diplomatic actors, both from representative institutions in the US and the central government.